Fragile Image Watermarking For Medical Images - Jasni, Mohamad Zain; Nor Amizam, Jusoh (2006)
This paper will discuss security of medical images and review some work done regarding medical images. We will then propose a fragile watermarking scheme that can detect tamper and recover the image. Our method requires a secret key and a public chaotic mixing algorithm to embed and recover a tampered image. The scheme is also resilient to VQ attack. The purpose is to verify the integrity and authenticity of medical images. We used 800x600x8 bits ultrasound (US)greyscale images in our experiment. We test our algorithm for up to 50% tampered block. We obtained 100% recovery for spread-tampered block.